Sistem Upah Minimum Kabupaten Dalam Perspekti Islam (Studi Kasus Pada Upah Minimum Kabupaten Sidoarjo) - Rachmad FirmanSyah; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
Islam does not allow wages under the minimum level based on the basic needs of groups of workers; nor let their wage increases that exceed a certain level determined based on his contribution to production. Employers need workers to run its business to remain in existence, while workers need the work to make ends meet. Islam tries to create a fair balance between the two, both in terms of remuneration and protection of the interests of workers and employers. There are three parameters in Islam as basis in determining the appropriate wage system of sharia, namely Justice, Feasibility and Virtue. The state has important roles in giving attention to the workers in earning sufficient wages to sustain a level of decent living and not allow wages under the minimum levels.